The Implementation of Holistic Approach in Teaching Speaking by the Teacher of English Speaking at the Second and Fourth Semester of the English - Aan Nursifa Hamizan; Ida Wardani; Effendi Limbong (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2018)
There are a lot of students have low speaking ability. They have difficulties to speak because of thinking about grammatical rules and pronouncing certain English words. It makes them have difficulties in expressing their ideas in speaking. As a result, they prefer to be silent and not fully participate in the classroom activities. The purpose of this study was to know how the teacher implemented the holistic approach in teaching speaking at the second and fourth semester of the English Department. The design of this study was qualitative research. The sources of data were observation and interview. Instruments of this study were classrooms observations, video recorder, field notes, and interview. There were three main points in data analysis technique such as data reduction, data display, and conclusion drawing and verification. The findings of this research showed the process of the holistic approach to teaching speaking which was applied by the teacher. Based on the observations, the researcher found that the teacher had implemented all stages of the holistic approach. Even though, they were not optimal because some aspects of language were not included in some stages such as vocabulary and pronunciation. Furthermore, to promote students' fluency in speaking the teacher provided students a lot of opportunities to practice their speaking. The teacher also provided accuracy tests (grammar and text structure) to promote their ability for further speaking assignments. Feedbacks were given by the teacher after students finished practicing their speaking or accuracy test to help them find out their mistakes. Based on the result of this research, the researcher concluded the teacher implemented the holistic approach in teaching speaking.